Experimental study and analysis on behaviours and strategies of social groups and individuals. (July 2020) - Hu, Yanghui; Zhang, Jun; Xiao, Hanyi; Cao, Shuchao; Ren, Xiangxia; Liang, Xuanwen; Li, Hongliu; Song, Weiguo
Highlights: An experimental study was conducted to investigate pedestrian behaviors of social groups and individuals. The length of the walk paths for individuals was 2.2% longer than that of social groups. Different strategies were observed in the experiment. At the beginning, 98.8% pedestrians chose to walk straight to their destinations. Only 16.7% of pedestrians changed their initial strategy. Abstract: Multi-directional flows in pedestrian facilities involve several interactions and conflicts among pedestrians. To understand how one reaches his/her destination in a crowd with multidirectional movement, a series of experiments were performed at different densities by considering social groups. No significant difference was observed in speed between individuals and social groups in the experiment. However, the length of the walk paths for individuals was 2.2% longer than that of social groups. Different strategies were observed for pedestrians to reach their destinations in the experiment. At the Prophase Free Movement stage, 98.8% of pedestrians walked straight to their destinations. In the Multidirectional Restricted Movement stage, 41% of pedestrians made detours to reduce their movement time, especially for individuals. In the movement with stopping, 83.3% of pedestrians preferred their initial strategy (straight strategy) and 16.7% of pedestrians changed their initial strategy to make detours and it could reduce their movement time. Our findings can be used to have a deep understanding on pedestrian dynamics and enhance the crowd management strategies.